Women’s Narratives of Trauma: (Re)storying Uncertainty, Minimization and Self-Blame - Brown, Catrina (Narrative Works, 2013)
Women’s stories of trauma often reveal uncertainty, minimization, and self-blame. This paper explores community-based research findings on women’s narratives illustrating powerful, yet uncertain, stories of chronic, multiple, and severe trauma. This paper argues that 1) research needs to recognize that posttraumatic responses often involve uncertainty and ambivalence about telling stories of trauma; 2) uncertainty is not just a product of trauma but also reflects the influence of the dominant discourse on women and trauma that creates fragmented memory of the events and supports blaming women for the violence and minimizing the serious of the violence; 3) uncertainty reveals the dangers of speaking and often a struggle with speaking and hiding simultaneously; and 4) research questions can be designed to counterview dominant discourse which will bring forward the prevalence and nature of the violence.